Sources and studies on the historical geography of ancient and medieval settlements in the Syr Darya, Talas, and Semirechye areas - T.Z. , Kaiyrken; Z.S. , Ilyassova; A. , Alibekuly (BULLETIN of the L.N. Gumilyov Eurasian National University. Historical sciences. Philosophy. Religion Series, 2023)
The article reveals information from Chinese, Arabic and Persian sources on the historical geography of ancient and medieval settlements in Syr Darya, Talas and Semirechye areas. It also reports on the introduction of this information into academic circulation, as well as on the scientists’ judgments regarding these sources. Thus, the article covers the official written sources included in The Twenty-four Histories, travel notes of such travellers as Xuánzàng, Jiǎ Dān, Dù Huán, works by medieval Arab authors Ibn Khordadbeh, Ibn al-Faqih, Qudama ibn Ja’far, al-Balkhi, Ibn Hawqal, Al-Maqdisi, al-Idrisi and Yaqut al-Hamaawi, and later works in Persian by Ala ad-Din Atâ-Malek Juvayni, Rashid al-Din, Jamal Karshi, Muhammad Haydar Dulati and Sharafeddin Ali Yazdi all related to ancient cities and settlements in the Syr Darya, Talas, Chu, Semirechye areas, and Eastern Tian-Shan. Accentuating these works, the authors analyze their potential and reliability, the complementarity of the data given and their unique features. Furthermore, the article presents source data about Kazakhstan and adjacent territories, namely about Eastern Tian-Shan and Kashgaria, and ancient cities along Syr Darya , collected by world’s academics, and shows the advantages and disadvantages of historical and geographical research based on this data. Such analysis contributes to further development of source study and historiography, which has originated in domestic science relatively recently and is now actively developing. The article analyses works by Michael Yang de Gu, Song Xian, V.Minorsky, H.Yule, Zhang Xingliang, Feng Chengjun, Cen Zhongmian, Zhou Liankuan, Th.Watters, V.V.Barthold, A.G.Malyavkin, P.Pelliot, A.M.Belenitsky, E.Chavannes, S.L.Volin, Matsuda Hisau, B.E.Komekov, R.B.Komekova, et alia.